ANALISIS PRESTASI BELAJAR MELALUI LAYANAN BIMBINGAN BELAJAR PADA SISWA DI RT 5 RW 3 PALUR DESA NGRINGO TAHUN 2021 - Rustika Damarwati; Lydia Ersta Kusumaningtyas (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2021)
The purpose of this study is to analyze whether the existence of tutoring services can provide increased learning achievement to students living in RT 5RW 3 Palur, Ngringo in 2021. This research was carried out in Ngringo, Palur, Jaten sub-district, Karanganyar. The research subjects were 2 students who had problems with low learning achievement. This research is a qualitative descriptive research and the research strategy in data analysis. Data collection techniques in this study were interviews, observation, and documentation. The validity of the data using triangulation techniques. Meanwhile, this research was conducted by interactive qualitative data analysis. Based on the results of the study, it could be seen that there wes an increase in learning achievement after 2 students attended tutoring services. But the increase in performance could not last if no follow-up was carried out. Thus, it can be concluded that there is an increase in learning achievement through the provision of tutoring services to students. Key Words: Learning Achievement, Tutoring Service.